2013
DOI: 10.1016/j.jpain.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Inhibition of Somatic Pain Is Impaired in Girls With Irritable Bowel Syndrome Compared With Healthy Girls

Abstract: Endogenous pain-inhibition is often deficient in adults with chronic pain conditions including irritable bowel syndrome (IBS). It is unclear whether deficiencies in pain-inhibition are present in young children with IBS. The present study compared endogenous pain-inhibition, somatic pain threshold, and psychosocial distress in young girls with IBS versus controls. Girls with IBS did not show significant endogenous pain-inhibition of heat pain-threshold during a cold-pressor task in contrast to controls who had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 63 publications
(134 reference statements)
4
55
0
2
Order By: Relevance
“…In a small sample of pre-menarchal girls, Williams, et al found no difference in heat pain threshold or in supra-threshold cold-pressor pain intensity, but evidence of impaired endogenous pain inhibition in IBS patients compared to healthy controls. 56 However, the latter result was not significant after controlling for psychological distress symptoms. As the authors note, this may be due to lack of statistical power.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a small sample of pre-menarchal girls, Williams, et al found no difference in heat pain threshold or in supra-threshold cold-pressor pain intensity, but evidence of impaired endogenous pain inhibition in IBS patients compared to healthy controls. 56 However, the latter result was not significant after controlling for psychological distress symptoms. As the authors note, this may be due to lack of statistical power.…”
Section: Discussionmentioning
confidence: 90%
“…Few studies have examined somatic pain sensitivity among children with chronically recurring abdominal pain, and only one including pediatric IBS patients. 1,17,18,56,60 Results from these studies have been equivocal, possibly due to the relatively small samples sizes. Furthermore, there are no prospective studies of pain sensitivity among children with recurrent abdominal pain and IBS, but increased somatic pain sensitivity was found in one study among adolescents and young adults with a history of childhood chronic abdominal pain.…”
Section: Introductionmentioning
confidence: 98%
“…For this analyses, the assumption of homogeneity of regression slopes was met. Recent evidence of mean differences in CPM between girls with and without IBS (d = 0.71) suggests that a minimum of 53 adolescents per group would be necessary to detect CPM effects [52]. Based on evidence of individual differences in pain rating changes across conditioning trials during CPM procedures [29], we examined within-individual changes in pain ratings from the mean pre-conditioning rating across the three conditioning trials.…”
Section: Data Analytic Planmentioning
confidence: 99%
“…Normality assumptions were checked using a Q-Q plot of residuals. Exploratory analyses examined the distribution of CPM effects in FAP and healthy youth based on prior work suggesting significant variability in the strength and direction of these effects [52,56]. Three FAP youth were taking selective serotonin reuptake inhibitors at the time of their laboratory visit; removing them from analyses did not significantly alter any results.…”
Section: Data Analytic Planmentioning
confidence: 99%
See 1 more Smart Citation